2015
DOI: 10.1007/s11325-015-1239-2
|View full text |Cite
|
Sign up to set email alerts
|

Oral health in patients treated by positive airway pressure for obstructive sleep apnea: a population-based case–control study

Abstract: Oral health of OSA patients treated by CPAP/BiPAP is comparable to that of matched controls in terms of amount of plaque, gingival inflammation, and masticatory function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…The validation of the FV2 questionnaire was performed against a periodontal diagnosis based on a full‐mouth periodontal examination. This was conducted in a prospective study conducted in a convenient sample of individuals seen at the Centre d'investigations préventives et cliniques of Paris (validation sample) (Adolph et al., ; Carra et al., , ; Darnaud, Thomas, Pannier, Danchin, & Bouchard, ). The IPC medical centre is subsidized by the French National Healthcare System ( Caisse Nationale d'Assurance Maladie ) and provides free medical and dental examinations to people living in Paris and surrounding areas.…”
Section: Methodsmentioning
confidence: 99%
“…The validation of the FV2 questionnaire was performed against a periodontal diagnosis based on a full‐mouth periodontal examination. This was conducted in a prospective study conducted in a convenient sample of individuals seen at the Centre d'investigations préventives et cliniques of Paris (validation sample) (Adolph et al., ; Carra et al., , ; Darnaud, Thomas, Pannier, Danchin, & Bouchard, ). The IPC medical centre is subsidized by the French National Healthcare System ( Caisse Nationale d'Assurance Maladie ) and provides free medical and dental examinations to people living in Paris and surrounding areas.…”
Section: Methodsmentioning
confidence: 99%
“…There is a moderate certainty of evidence that individuals who are obese or overweight and those with the metabolic syndrome have a higher risk of both gingivitis and periodontitis (Nibali et al 2013, Range et al 2013, Keller et al 2015, Gaio et al 2016. Patients with obstructive sleep apnoea and other sleep disorders have an enhanced risk of periodontal diseases, however, the level of certainty is low (Keller et al 2013, Lee et al 2014, Sanders et al 2015, Carra et al 2016.…”
Section: Cardio-metabolic Disordersmentioning
confidence: 99%
“…The risk factors that increase gingivitis and periodontitis risk in patients with OSAS, regardless of obesity, are snoring, mouth opening for long periods of time, and tobacco use. Other studies showed that the association between snoring and periodontal diseases was strong when the patients with diabetes were excluded 10 , 48 . When excluding patients with diabetes, a recent study showed that snoring was significantly associated with periodontitis 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The association between periodontal diseases and OSAS is still unclear. Recent studies attempted to establish this association in different populations 13 , 48 , 49 . The comparison among studies is imprecise because of the different methodologies adopted in each one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation